Empowerment of Santri in Reality and Recollection: Study in Pesantren Hubulo, Gorontalo - Idham (Jurnal Pendidikan Islam, 2016)
This article is a summary of the result of the research about the empowerment of santri in Pondok Pesantren Hubulo (PP Hubulo) or Hubulo Islamic Boarding School in Gorontalo Province. The research questions are 1. what kind of empowerment of santri (student of Islamic boarding school) was implemented by PP Hubulo Gorontalo Province; 2. how were the prospect and challenge facing PP Hubulo Gorontalo Province in empowering its santri. The results of research showed that, 1) when empowerment was understood as how santri had power and strength, then actually all of the activities in PP Hubulo were the empowerment of santri. However, when empowerment was divided into two categories, namely soft skill and hard skill, then what existed in PP Hubulo was soft skill only, and 2) there were some factors being the obstacles in the empowerment of santri, among others was the unavailable time, where PP Hubulo used three curricula at the same time, not to mention the demands of national examination that cause the empowerment of santri’s hard skill became impossible to be implemented.